Role of biodegradation in the removal of pharmaceutically active compounds with different bulk organic matter characteristics through managed aquifer recharge: Batch and column studies - Maeng, Sung Kyu; Sharma, Saroj K.; Abel, Chol D. T.; Magic-Knezev, Aleksandra; Amy, Gary L. (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Natural water treatment systems such as bank filtration have been recognized as providing effective barriers in the multi-barrier approach for attenuation of organic micropollutants for safe drinking water supply. In this study, the role of biodegradation in the removal of selected pharmaceutically active compounds (PhACs) during soil passage was investigated. Batch studies were conducted to investigate the removal of 13 selected PhACs from different water sources with respect to different sources of biodegradable organic matter. Neutral PhACs (phenacetine, paracetamol, and caffeine) and acidic PhACs (ibuprofen, fenoprofen, bezafibrate, and naproxen) were removed with efficiencies greater than 88% from different organic matter water matrices during batch studies (hydraulic retention time (HRT): 60 days). Column experiments were then performed to differentiate between biodegradation and sorption with regard to the removal of selected PhACs. In column studies, removal efficiencies of acidic PhACs (e.g., analgesics) decreased under conditions of limited biodegradable carbon. The removal efficiencies of acidic PhACs were found to be less than 21% under abiotic conditions. These observations were attributed to sorption under abiotic conditions established by a biocide (20 mM sodium azide), which suppresses microbial activity/biodegradation. However, under biotic conditions, the removal efficiencies of these acidic PhACs were found to be greater than 59%. This is mainly attributed to biodegradation. Moreover, the average removal efficiencies of hydrophilic (polar) neutral PhACs (paracetamol, pentoxifylline, and caffeine) with low octanol/water partition coefficients (log K-ow less than 1) were low (11%) under abiotic conditions. However, under biotic conditions, removal efficiencies of the neutral PhACs were greater than 98%. In contrast, carbamazepine persisted and was not easily removed under either biotic or abiotic conditions. This study indicates that biodegradation represents an important mechanism for the removal of PhACs during soil passage. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: WASTE-WATER EFFLUENTS; AQUATIC ENVIRONMENT; BANK FILTRATION; CARE PRODUCTS; DRINKING; FATE; CONTAMINANTS; RESIDUES; FLUORESCENCE; BEHAVIOR